Diagnostic criteria for fetal growth restriction: sensitivity, specificity and clinical role across gestation. (3rd August 2021) - Dall'Asta, A.; Frusca, T.; Ghi, T.
Abstract : Linked article: This Correspondence comments on Roeckner et al. Click here to view the article.